2024
DOI: 10.3390/agriengineering6010020
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral Response of the Soybean Crop as a Function of Target Spot (Corynespora cassiicola) Using Machine Learning to Classify Severity Levels

José Donizete de Queiroz Otone,
Gustavo de Faria Theodoro,
Dthenifer Cordeiro Santana
et al.

Abstract: Plants respond to biotic and abiotic pressures by changing their biophysical and biochemical aspects, such as reducing their biomass and developing chlorosis, which can be readily identified using remote-sensing techniques applied to the VIS/NIR/SWIR spectrum range. In the current scenario of agriculture, production efficiency is fundamental for farmers, but diseases such as target spot continue to harm soybean yield. Remote sensing, especially hyperspectral sensing, can detect these diseases, but has disadvan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…A study on the hyperspectral response of soybean cultivars to target spot disease conducted by Otone et al [23] used machine learning for severity classification. Using data collected with fungicides for various diseases during the 2022-2023 agricultural season, the research found that SVM and RF were effective in classifying disease severity with 85% and 76% accuracy, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study on the hyperspectral response of soybean cultivars to target spot disease conducted by Otone et al [23] used machine learning for severity classification. Using data collected with fungicides for various diseases during the 2022-2023 agricultural season, the research found that SVM and RF were effective in classifying disease severity with 85% and 76% accuracy, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The SIF-GPP relationship was highly dependent on the PFT. In addition, as different varieties may respond differently to environmental factors, it would be beneficial to consider the effects of the specific cultivars or genotypes [55][56][57]. Overall, it suggests that different PFTs may perform differently when utilizing PRI to enhance the SIF t -GPP relationship.…”
Section: Limitations and Implicationsmentioning
confidence: 99%